2017
DOI: 10.1002/adfm.201605058
|View full text |Cite
|
Sign up to set email alerts
|

Air‐ and Active Hydrogen‐Induced Electron Trapping and Operational Instability in n‐Type Polymer Field‐Effect Transistors

Abstract: Organic field‐effect transistors (OFETs) have attracted much attention for the next‐generation electronics. Despite of the rapid developments of OFETs, operational stability is a big challenge for their commercial applications. Moreover, the actual mechanism behind the degradation of electron transport is still poorly understood. Here, the electrical characteristics of poly{[N,N‐9‐bis(2‐octyldodecyl)‐naphthalene‐1,4,5,8‐bis(dicarboximide)‐2,6‐diyl]‐alt‐5,59‐(2,29‐bithiophene)} (P(NDI2OD‐T2)) thin‐film transist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The last few decades have witnessed the rise of semiconducting, all-organic polymers as excellent metal-free and visible light-active materials for various optoelectronic and energy harvesting applications . Although impressive improvements in performance have been achieved, particularly for plastic solar cells, the synthesis procedures for semiconducting polymers are cumbersome and difficult to scale up, and the organic semiconductors themselves are unstable under the action of heat, light and/or ambient air . Consequently, there are scalability concerns related to semiconducting polymers, and requirement of heavy encapsulation to achieve even modest durability in the photovoltaic application.…”
Section: Introductionmentioning
confidence: 99%
“…The last few decades have witnessed the rise of semiconducting, all-organic polymers as excellent metal-free and visible light-active materials for various optoelectronic and energy harvesting applications . Although impressive improvements in performance have been achieved, particularly for plastic solar cells, the synthesis procedures for semiconducting polymers are cumbersome and difficult to scale up, and the organic semiconductors themselves are unstable under the action of heat, light and/or ambient air . Consequently, there are scalability concerns related to semiconducting polymers, and requirement of heavy encapsulation to achieve even modest durability in the photovoltaic application.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22,26 ] The density of water trap states in the channel—a common cause of mobility reduction [ 27 ] and operating voltage increase [ 28 ] —is also reduced due to the increased surface hydrophobicity. [ 29 ] Accordingly, transistors fabricated on ODTS‐treated gate oxide usually show higher carrier mobility than on bare gate oxide. For example, pentacene FETs fabricated on ODTS‐treated gate oxides resulted in a field‐effect mobility of 1.5 cm 2 V −1 s −1 , while bare gate oxide devices showed field‐effect mobilities of 0.7 cm 2 V −1 s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…In a full FET, we observed that the trapping mainly occurs near the source contact (Figure S10, Supporting Information), suggesting that the trapped charges mainly come from the source electrode. This impact is not due to the degradation, and the chemical and electrochemical instability of semiconductor that directly trapping the mobile carriers (Figure S11, Supporting Information) …”
mentioning
confidence: 99%